Effects of biomass burning and photochemical oxidation on the black carbon mixing state and light absorption in summer season. (1st March 2021) - Wang, Tiantian; Zhao, Gang; Tan, Tianyi; Yu, Ying; Tang, Rongzhi; Dong, Huabin; Chen, Shiyi; Li, Xin; Lu, Keding; Zeng, Limin; Gao, Yaqin; Wang, Hongli; et al.
Abstract: To investigate the effects of biomass burning and photochemical oxidation on the black carbon (BC) mixing state and light absorption, a tandem centrifugal particle mass analyzer (CPMA) and single-particle soot photometer (SP2) system was used to measure ambient fine particulate BC during EXPLORE-YRD 2018 campaign (EXP eriment on the eL ucidation of the atmospheric O xidation capacity and aerosol foR mation, and their E ffects in Yangtze River Delta). The mass ratio (MR ) of the non-BC coating to BC core, a morphology-independent parameter to quantify the mixing state of BC-containing aerosols, is derived. Two types of periods were identified, namely non-significant biomass-burning period (NB), and enhanced biomass burning period (EB). The MR was higher during EB (2.3 ± 0.5), compared with during the NB (2.0 ± 0.5). MR showed bimodal diurnal variation with peaks in the early morning and early afternoon, mainly due to the biomass burning and photochemical processes, respectively. The light-absorbing enhancement ranged from 1.0 to 1.19 when MR was from 1.4 to 3.4. The relationship of rBC mixing state and its optical properties was parameterized, which can further be used in the regional model. Highlights: BC coating-to-core Mass ratio was quantified using a tandem CPMA - SP2 system, with an average of 2.2 ± 0.5 during the campaign. Photochemical processing played a dominant role in changing coating amount and light absorption of BC in the summer daytime. The relationship of rBC mixing state and its optical properties (Eabs ) was parameterized.